2017
DOI: 10.1097/md.0000000000006248
|View full text |Cite
|
Sign up to set email alerts
|

High expression of SALL4 and fascin, and loss of E-cadherin expression in undifferentiated/dedifferentiated carcinomas of the endometrium

Abstract: Undifferentiated/dedifferentiated endometrial carcinomas (UCE/DCEs) of the endometrium are rare tumors with poor prognosis. There are few clinicopathologic studies with detailed immunohistochemical analysis regarding UCE/DCEs.We evaluated the diagnostic value of a selected tumor stem-cell marker and epithelial-mesenchymal transition (EMT) markers, in addition to previously studied markers in identifying UCE/DCEs from other types of high-grade endometrial carcinomas.Eleven cases of UCE/DCEs with complete clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
(52 reference statements)
3
13
2
Order By: Relevance
“…These results mirror those published in the DEC-LG literature, showing that loss of epithelial markers, PAX8 and ER are in keeping with the process of dedifferentiation. 5,6,17,26 We have also investigated the expression of claudin-4, an epithelial tight junction protein previously shown to be lost in DEC-LG, predominantly in the SWI/SNF-deficient subset. 27 We have found a similar expression pattern in our series, with predominantly negative staining in the DEC component of both LG and HG groups.…”
Section: Discussionmentioning
confidence: 99%
“…These results mirror those published in the DEC-LG literature, showing that loss of epithelial markers, PAX8 and ER are in keeping with the process of dedifferentiation. 5,6,17,26 We have also investigated the expression of claudin-4, an epithelial tight junction protein previously shown to be lost in DEC-LG, predominantly in the SWI/SNF-deficient subset. 27 We have found a similar expression pattern in our series, with predominantly negative staining in the DEC component of both LG and HG groups.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al ( 1 ) described morphologic features of DEAC in 2006 and it was included in the 2014 version of the book, ‘World Health Organization Classification of the Tumors of Female Reproductive Organs’ ( 5 ). Although DEAC is generally presented as case reports, a series of such tumors was recently reported in the literature ( 6 , 7 , 8 , 9 , 10 , 11 , 12 ). DEAC primarily occurs during the 6 th and 7 th decades; consistent with previous studies, the mean age at diagnosis in our study was 58 years ( 11 , 12 , 13 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although DEAC is generally presented as case reports, a series of such tumors was recently reported in the literature ( 6 , 7 , 8 , 9 , 10 , 11 , 12 ). DEAC primarily occurs during the 6 th and 7 th decades; consistent with previous studies, the mean age at diagnosis in our study was 58 years ( 11 , 12 , 13 , 14 , 15 ). Similar to existing studies, all patients in our study underwent TAH+BSO and PL ( 1 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al [19] found diffuse fascin expression in the undifferentiated component of 94% of cases of dedifferentiated endometrial carcinomas. Onder et al [20] found diffuse expression of fascin in 82% of cases and loss of E-cadherin expression in 55% of cases.…”
Section: Discussionmentioning
confidence: 97%